Cadmium-associated molecular pathways drive gender-specific pathogenesis and prognosis in lung adenocarcinoma - Yusi Yang; Zhiyuan Zhang; Xing He; Zhiya Li; Lin Lu; Yiguo Jiang; Yueting Shao (Ecotoxicology and Environmental Safety)
Lung adenocarcinoma (LUAD) demonstrates pronounced female predominance and escalating incidence, yet sex-specific environmental determinants remain poorly characterized. This study elucidates cadmium (Cd)-associated molecular mechanisms driving female LUAD pathogenesis through integrated epidemiological and bioinformatics analyses. National Health and Nutrition Examination Survey (NHANES) data revealed elevated blood Cd levels in female lung cancer patients versus controls (P < 0.05), showing strong correlation with urinary albumin (ALB; r = 0.62, P < 0.05). Cross-referencing Comparative Toxicogenomics Database (CTD) and The Cancer Genome Atlas (TCGA) databases identified 11 Cd-responsive differentially expressed genes (DEGs) in early-stage female LUAD. ALB exhibited significant upregulation in female early-stage tumors compared to non-early-stage female LUAD and male counterparts (P < 0.05). Functional analyses revealed ALB's involvement in lipid transport regulation and metal ion homeostasis. GEO data (GSE32863) confirmed sex-specific dysregulation patterns: ALB upregulation (P < 0.01) contrasted with CEL and MPO downregulation in female LUAD (P < 0.05), a finding corroborated by quantitative reverse transcription polymerase chain reaction (qRT-PCR). Cox regression and concordance index analyses identified lipid transport pathways as key prognostic determinants (C-index>0.8), while SERPINA5 emerged as a novel prognostic biomarker for early-stage female LUAD (HR=1.59, 95 % CI:1.06–2.40, P = 0.03). We propose a Cd-exposure pathogenesis model wherein disrupted ALB homeostasis triggers aberrant lipid trafficking and SERPINA5-mediated signaling cascades, driving sexual dimorphism in LUAD progression. These findings provide mechanistic insights into environmental carcinogen-induced sex disparities, highlighting ALB and SERPINA5 as potential targets for gender-specific diagnostic strategies and therapeutic development.